2019
DOI: 10.15503/jecs20192.32.42
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Concept of a Good School With Teachers’ Characteristics in the Context of a Good School Concept

Abstract: Aim. The concept of Good School was formed in 2015, however, the implementation of it has been rather slow. Therefore, the research aim of this article is to identify the educational experts’ viewpoints on the concept. The following questions have been raised to specify the aim: if the concept of the school of general education, presented as Good School, is adequately understood, what features should a teacher have in order to implement the concept of Good School? Methods. To answer the research question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Kanjee (2018) reported that student teachers felt that their lecturers needed to visit them more often for the purpose of providing clarity in cases where they were confused. This somewhat confirms what Kriauciuniene and Targamadze (2019) said regarding the necessity for mentoring and supervision for student teachers.…”
Section: Shortcomings Of Teaching Practicum As a Component Of Itesupporting
confidence: 87%
See 2 more Smart Citations
“…Kanjee (2018) reported that student teachers felt that their lecturers needed to visit them more often for the purpose of providing clarity in cases where they were confused. This somewhat confirms what Kriauciuniene and Targamadze (2019) said regarding the necessity for mentoring and supervision for student teachers.…”
Section: Shortcomings Of Teaching Practicum As a Component Of Itesupporting
confidence: 87%
“…A well-functioning school may be characterized as one with quality infrastructure (Alzahrani, et al 2016), effective school management and leadership (Leithwood, 2016), considerable attempt to realise the mission and vision of the school (Kirk & Jones, 2004), well-trained teachers who can serve as mentors or supervisors (Kriauciuniene & Targamadze, 2019), and many other factors.…”
Section: Benefits Of Teaching Practicum As a Component Of Itementioning
confidence: 99%
See 1 more Smart Citation